The Current State of the Art and Advancements, Challenges, and Future of Additive Manufacturing in Aerospace Applications - Melkamu Tadesse Getachew; Menberu Zeleke Shiferaw; Bekalu Sintayehu Ayele (Advances in Materials Science and Engineering)
Additive manufacturing has revolutionized the manufacturing industry, particularly in aerospace. This paper provides an overview of the advancements, state-of-the-art, challenges, and future of additive manufacturing in the aerospace industry. It begins by discussing the workflow of additive manufacturing and the comparison of software required for modeling and slicing the designed models. Various types of additive manufacturing processes used in the aerospace industry with their postprocessing challenges and solutions are also presented in detail. Besides, the challenges and limitations that come with the use of additive manufacturing in aerospace are also outlined. The paper investigated that the use of additive manufacturing in aerospace has given several advantages such as the ability to produce complex geometries, reduce material waste, and improve design flexibility. The future of additive manufacturing in aerospace looks promising, with the potential for even more cost-effective and efficient production. The paper concludes that additive manufacturing has proven to be a game-changer in aerospace presenting different advanced aerospace components in detail, with continued research and development shaping the future of manufacturing and production. With advancements in technology and processes, additive manufacturing for aerospace can overcome the challenges and become a reliable and cost-effective alternative to traditional manufacturing methods.